Cell stiffness determined by atomic force microscopy and its correlation with cell motility - Luo, Qing; Kuang, Dongdong; Zhang, Bingyu; Song, Guanbin (Biochimica et biophysica acta, 2016)
Cell stiffness is a crucial mechanical property that is closely related to cell motility. AFM is the most prevalent method used to determine cell stiffness by the quantitative parameter designated as Young's modulus. Young's modulus is regarded as a biomarker of cell motility, especially in estimating the metastasis of cancer cells, because in recent years, it has been repeatedly shown that cancerous cells are softer than their benign counterparts. However, some conflicting evidence has shown that cells with higher motility are sometimes stiffer than their counterparts. Thus, the correlation between cell stiffness and motility remains a matter of debate. In this review, we first summarize the reports on correlations between cell motility and stiffness determined by AFM and then discuss the major determinants of AFM-determined cell stiffness with a focus on the cytoskeleton, nuclear stiffness and methodological issues. Last, we propose a possible correlation between cell stiffness and motility and the possible explanations for the conflicting evidence. The AFM-determined Young's modulus is greatly affected by the characteristics of the cytoskeleton, as well as the procedures and parameters used in detection. Young's modulus is a reliable biomarker for the characterization of metastasis; however, reliability is questioned in the evaluation of pharmacologically or genetically modified motility. This review provides an overview of the current understanding of the correlation between AFM-determined cell stiffness and motility, the determinants of this detecting method, as well as clues to optimize detecting parameters. •Conflicting reports about correlation between motility and stiffness are summarized.•The determinants of the AFM-determined stiffness are discussed.•Crucial methodological issues in the AFM detection are suggested.•The possible reasons for the existence of the conflicting reports are proposed.